PERANAN TURNAMEN BERBASIS ICT DENGAN APLIKASI QUIZIZZ TERHADAP PEMBELAJARAN KIMIA - Sri Wilda Albeta; Nofianti Nofianti; Sri Rahmandani (Jurnal Pendidikan Kimia Universitas Riau, 2020)
ICT bases tournament with quizizz application has role play to chemistry leaning study. This role can be seen from motivation and student assessment aspect. This research is design experimental quasi “The randomized pre test-post test control group design” and the data analysis is using t-test for comparing experiment and control class. Learning with this bases can improve the motivation and result of student learning. Students believe that they can be the best in study with this quizizz application. It becomes the wonderful time to study with excited, happy, and the material is easy to understand. Beside that, with ICT function, students can apply this tournament is out of the schedule time to study, so it can be doing at anywhere and anytime